BENZOFURAN SÜBSTİTÜE ?,SS-DOYMAMIŞ KETONLAR VE TÜREVLERİNİN SENTEZİ - COŞKUN, DEMET (Fırat Üniveristesi, 2008)
Bu çalışmada, kalkonlar (?, ß-doymamış ketonlar), farklı aldehit türevleri; salisil aldehit, 3-nitro benzaldehit, 2-hidroksi benzaldehit, 3-hidroksi benzaldehit, 4-hidroksi benzaldehit, 4-dimetilamino benzaldehit, tereftalaldehit, tiyofen-2-karboksaldehit, 2-flor benzaldehit, 3-flor benzaldehit, benzaldehit, 5-brom salisil aldehit, 2-furankarbaldehit, pirol-2-karbaldehit ve 1-(1-benzofuran-2-il) etanon' un baz olarak NaOH varlığında Claisen-Schmidt kondenzasyonuyla sentezlendi.Üç aldehit türevi; 4-hidroksi benzaldehit, tereftalaldehit ve vanilin'den kalkonları elde etmek için katalizör olarak BF3.Et2O kompleksi kullanıldı.Farklı açil halojenürler; klor asetilklorür, brom asetilbromür ve metakriloil klorür ile sübstitüe hidroksi kalkonların, Et3N varlığında reaksiyonuyla kalkon içeren ?-haloester türevleri sentezlendi.2-Pirazolin türevleri, kalkonlar ve hidrazin monohidratın reaksiyonundan elde edildi. Pirazolin kısmı içeren ?-haloamitler, elde edilen pirazolin türevleri ve klorasetil klorürün , Et3N varlığında reaksiyonundan sentezlendi.Sentezlenen tüm bileşiklerin yapı analizleri FT-IR, 1H ve 13C-NMR spektroskopik teknikleriyle aydınlatıldı. Bu bileşiklerin erime noktaları ve elementel analiz değerleri de tayin edildi.

In this study, chalcones (?,ß-unsaturated ketones) were synthesized with Claisen-Schmidt condensation of 1-(1-benzofurane-2-yl) ethanone (starting compound) and different aldehyde derivatives; benzaldehyde, 2-hydroxy benzaldehyde, 3-hydroxy benzaldehyde, salicyl aldehyde, terephthaldehyde, thiophene-2-carboxaldehyde, 2-fluorobenzaldehyde, 3-fluorobenzaldehyde, 5-bromo salicyl aldehyde, 2-furaldehyde, pyrrole-2-carboxaldehyde, 4-dimethylamino benzaldehyde, 3-nitro benzaldehyde in the presence of NaOH as base.Three aldehyde derivatives; 4-hydroxy benzaldehyde, terephthaldehyde and vanilin weren?t reacted with this method. Therefore, a different method was used so as to obtain to chalcones of this three aldehyde derivatives. In this method, BF3.Et2O complex was used as catalyst.?-Haloesters containing moiety chalcone were synthesized from the reaction of substituted hydroxyl chalcones with different acylating agents; chloroacetyl chloride, bromoacetyl bromide and methacryloyl chloride in the presence of Et3N.2-Pyrazoline derivatives were obtained from the reaction of the chalcones with hydrazine monohydrate. ?-haloamides containing moiety pyrazoline were synthesized from the reaction of the pyrazoline derivatives with chloro acetylchloride in the presence of Et3N.The chemical structures of all the compounds were identified by FT-IR, 1H and 13C-NMR spectroscopic techniques. Melting point and elemental analyses values of these compounds were also determined.
The synthesis of benzofurane substituted ?,ß-unsaturated ketones and their derivatives
Keywords: Kimya